A nemfogyasztás/nemvásárlás motivációi, értelmezése a turizmusban - Törőcsik, Mária; Csapó, János (Vezetéstudomány / Budapest Management Review, 2021)
The reasons and motives behind non-consumption/non-purchase pose a rather exciting interpretational and research question in general, but particularly in the case of certain markets and in the field of tourism. From the point of view of consumers’ motivations, the authors differentiate two types of non-consumption/non-purchase behaviour: abnegation and dropout. Dropping out can usually be related to a shortage situation, while the source of abnegation is a conceptual, respective decision. In their study, besides general revealing the motivations for non-consumption/non-purchase, they focus on the kind of characteristics appearing in tourism in the scope of non-consumers/non-purchasers and how they can determine and systematize these groups’ background. Realizing the practical and professional actuality and relevance of the topic, the aim of the present study is to introduce this less reviewed topic into professional literature, primarily with the aim of starting a new direction of thinking among the different disciplines, initially for researchers and representatives of marketing and tourism. Their conceptual ideas are supported by the results of a representative and great sample questionnaire survey.